2007
DOI: 10.1002/adma.200602303
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous IR Material Recognition and Conductivity Mapping by Nanoscale Near‐Field Microscopy

Abstract: Nanostructures are at the heart of ever-shrinking electronic and photonic devices. The engineering of nanocomposite materials, building blocks, [1,2] and conduction properties [3,4] necessitate advanced microscopy tools to assess critical dimensional, compositional, structural, and conduction properties for analysis and quality control. [5] Here we demonstrate with industrial bipolar and metal-oxide-semiconductor (MOS) devices that mid-IR scattering-type near-field optical microscopy (s-SNOM) [6,7] has the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 39 publications
3
71
0
Order By: Relevance
“…Following their work done in the near-infrared regime [50], Keilmann's group at the Max Planck Institute of München developed its own approach: they collect the scattered field in the back-scattered direction placing a cantilevered W tip, used in tapping AFM mode, at the focus of a paraboloid mirror as shown in Fig. 9c [51].…”
Section: Metal Tip-near-f Ield Collectionmentioning
confidence: 99%
“…Following their work done in the near-infrared regime [50], Keilmann's group at the Max Planck Institute of München developed its own approach: they collect the scattered field in the back-scattered direction placing a cantilevered W tip, used in tapping AFM mode, at the focus of a paraboloid mirror as shown in Fig. 9c [51].…”
Section: Metal Tip-near-f Ield Collectionmentioning
confidence: 99%
“…As already mentioned, a doping gradient can be determined from just a single near-field image [34]. The extraction of the scattering contrast along the gradient results in resonance curves akin to those in Fig.…”
Section: Apertureless Near-field Microscopy Development From Microwavmentioning
confidence: 99%
“…Further work with mid-infrared s-SNOM has confirmed that the local conductivity contrast can indeed be quantified along a doping gradient, by imaging a series of real-world nanostructured device samples produced by microelectronics industry [34]. For this a sample containing transistor elements was prepared by polishing, and SEM was used to visualize the position of the different elements of the nanocircuit.…”
Section: Apertureless Near-field Microscopy Development From Microwavmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the scattering radiation can be induced upon the presence of certain surface electromagnetic field. Surface plasmon wave (SPW) exemplifies such surface electromagnetic field, by which the evanescent wave propagates on the metal-dielectric or metal-vacuum interface [29,43,50]. In this section, the near-field characteristics of the SPW emanating from single hole or hole arrays of nanometer size made by focused ion beam on metal film are present.…”
Section: Applications In Nanophotonicsmentioning
confidence: 99%